Biological Control of Sheath Blight Disease of Rice by using Antagonistic Bacteria - Bashar, MA; Hossain, MA; Rahman, MM; Uddin, MN; Begum, MN (Bangladesh Journal of Scientific and Industrial Research, 2010)
The study was made to detect and identify antagonistic bacteria to control Rhizoctonia solani, a causal organism of sheath blight (ShB) disease of rice. Isolation of antagonistic bacteria was done from ShB infected rice leaf collected from the districts of Gazipur, Rajshahi, Bogra and Comilla. Fifty isolates of bacteria were isolated. These isolates were tested for antagonism against ShB pathogen of in PDA medium. Among the isolates of antagonistic bacteria (both fluorescent and non fluorescent), eleven produced more than 15 mm inhibition zone, were selected for this study. Remarkable inhibition zone producing ten isolates were selected to observe their antagonistic behaviour by soaking the sclerotia of Rhizoctonia solani and rice seedlings in different hours into bacterial suspension of 3.84 x 107 CFU/ml. Both the in vitro and in vivo rom showed that the sclerotial germination and sheath blight symptom expression were delayed 6-9 days. Soaking of both seedlings and sclerotia with the test bacteria was found most effective to control ShB (38% - 100%) than soaking of seedlings alone with bacterial suspension at different hours. However, BanShbFPS5 (2)B, BanShb738(3), BanShb738(2) and BanShb581(1), the four antagonistic bacterial isolates could be applied as biological agent to control sheath blight disease of rice and they could control sheath blight disease development and could delay the epidemics of the disease. Key words: Biological control; Sheath blight disease; Rhizoctonia solani; Antagonistic bacteria DOI: 10.3329/bjsir.v45i3.6529 Bangladesh J. Sci. Ind. Res. 45(3), 225-232, 2010